Spare and found parts - Griffin, Sarah Maria (Greenwillow Books, an imprint of HarperCollinsPublishers, 2016)
Nell Crane has never held a boy's hand. In a city devastated by an epidemic, where survivors are all missing parts--an arm, a leg, an eye--Nell has always been an outsider. Her father is the famed scientist who created the biomechanical limbs that everyone now uses. But she's the only one with her machinery on the inside: her heart. Since the childhood operation, she has ticked. Like a clock, like a bomb. And as her community rebuilds, everyone is expected to contribute to the society's good ... but how can Nell live up to her father's revolutionary ideas when she has none of her own? Then she finds a lost mannequin's hand while salvaging on the beach, and inspiration strikes. Can Nell build her own companion in a world that fears advanced technology? The deeper she sinks into this plan, the more she learns about her city--and her father, who is hiding secret experiments of his own. Sarah Maria Griffin's haunting literary debut will entrance fans of Patrick Ness' Chaos Walking series, Paolo Bacigalupi's Ship Breaker, and Emily St. John Mandel's Station Eleven.